THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS INTERVENING VARIABLE - Tanamal, Kartika; Pambelum, Yohanes Joni; Hidayah, Zainur (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2023)
This research aims to determine and analyze the Influence of Organizational Culture and Work Environment on Employee Performance with Job Satisfaction as the Intervening Variable (Case Study of the Laboratory Department at PT Indo Muro Kencana). The research uses a quantitative approach with a cross-sectional survey method. This study involved 63 employees of the Laboratory Department at PT Indo Muro Kencana as the population. The saturated sample, also known as a census, is a sampling technique when the entire population is used as a sample, therefore the sample of the research is 63 people. The analysis of research data uses path analysis with SPSS analysis equipment. The research results a significant positive direct effect of organizational culture on the job satisfaction of the Laboratory Department at PT. Indo Muro Kencana. The work environment has a significant positive direct impact on the job satisfaction of the Laboratory Department at PT. Indo Muro Kencana, The organizational culture has a significant positive immediate effect on the employee performance of Laboratory Department at PT. Indo Muro Kencana, The work environment also has a significant positive direct impact on the employee performance of Laboratory Department at PT. Indo Muro Kencana, The job satisfaction has a significant positive immediate effect on the employee performance of Laboratory Department at PT. Indo Muro Kencana while the organizational culture indirectly impacts employee performance in which the job satisfaction functioned as an intervening variable in the Laboratory Department at PT. Indo Muro Kencana. However, there is an indirect effect of the work environment on employee performance with job satisfaction as an intervening variable in the Laboratory Department at PT. Indo Muro Kencana.